Impact of a poison control center on the length of hospital stay of poisoned patients: retrospective cohort - Galvão, Tais Freire (2018)
Fundacao de Amparo a Pesquisa do Estado do Amazonas (FAPEAM, Research Support Foundation of the State of Amazonas)